The Influence of Interactive Learning Skills on Metacognitive Strategies Among College Students in Mathematics - Baog, Ismael W; Mendez, Pearl Charisse; Manzano, Jan Marie S (Yayasan Meira Visi Persada, 2025)
Metacognitive strategies in mathematics remain a challenge for many college students, impacting their ability to apply concepts effectively. This study examined the influence of interactive learning skills on metacognitive strategies among college students in mathematics. Using a descriptive-correlational research design, data were collected from 100 randomly selected students through validated questionnaires. Results indicated that interactive learning skills significantly enhance metacognitive strategies. However, findings suggest that motivation, instructional design, and learning preferences also influence metacognitive development. These results affirm Vygotsky’s Social Constructivist Theory (1978), emphasizing the role of collaboration in cognitive growth. Future research may explore additional factors affecting metacognitive strategies, and educators should integrate structured interactive learning techniques to strengthen students’ problem-solving abilities